(untitled) (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Stato Città del Vaticano e Unione europea. La Convenzione monetaria - 2. Lo sviluppo della SCV del Vaticano. Il dilatamento della giurisdizione vaticana e i rapporti di giurisdizione con l’Italia - 3. La normativa vaticana e il processo di valutazione MONEYVAL. Approccio collaborativo delle autorità vaticane e rapporti internazionali - 4. Gli sviluppi più recenti. International Relations of Vatican City State and measures in financial law ABSTRACT: After having outlined the peculiarities of Vatican City State’s nature, this paper examines the development of its financial law, starting with the Monetary Convention with European Union. The Holy See from 2009 makes a serious effort to adjust its law to the current needs of an increasingly globalised market. This results in a profound change in the Vatican international relations, which were previously mainly addressing Italy, in order to satisfy the territorial and material needs of a small State. Today Vatican City State has agreed to be subject to periodic controls on its financial system by international bodies. It has developed a system of international relations and it integrates into the global financial market transparency system.